2018
DOI: 10.5489/cuaj.5108
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive clinical factors in patients with metastatic castration-resistant prostate cancer treated with cabazitaxel

Abstract: Introduction: Cabazitaxel is one of several treatment options available for patients with metastatic castration-resistant prostate cancer who have progressed on docetaxel. Little is known about clinical factors that influence prognosis or treatment response for patients receiving cabazitaxel. Identifying prognostic and predictive factors could contribute to the optimal selection of patients for treatment after docetaxel. Methods: A retrospective review of patients enrolled on the cabazitaxel Canadian Early Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Also, patients with PCa after radical surgery have a high recurrence rate (30%) [ 16 ]. Currently, the treatment protocol for PCa depends on clinical and pathological prognostic biomarkers such as PSA, T staging, and Gleason score [ 17 ]. The National Comprehensive Cancer Network (NCCN) guidelines can stratify the risk of the patient and provide further diagnosis and treatment recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with PCa after radical surgery have a high recurrence rate (30%) [ 16 ]. Currently, the treatment protocol for PCa depends on clinical and pathological prognostic biomarkers such as PSA, T staging, and Gleason score [ 17 ]. The National Comprehensive Cancer Network (NCCN) guidelines can stratify the risk of the patient and provide further diagnosis and treatment recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common Grade ≥ 3 adverse events (AEs) associated with the use of cabazitaxel is neutropenia or febrile neutropenia [12,18,19] and, interestingly, there appears to be a correlation between efficacy and rates of Grade ≥ 3 neutropenia [20,21]. Other prognostic factors that have been reported to be associated with clinical outcomes in CRPC patients treated with cabazitaxel include site of metastasis [18,[22][23][24], Eastern Cooperative Oncology Group performance status (ECOG PS) [24,25], number of cabazitaxel treatment cycles [23], prior treatment history [18,26] and several laboratory measures [25,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is one of the most lethal cancers in the world, with low survival and poor prognosis (5). Several metabolomic studies have led to an enhanced understanding of disease mechanisms, and the discovery of novel diagnostic biomarkers (44,45). In the present study, it was found that 69 metabolites showed significant differences in OCT-embedded groups, and 23 metabolites were significantly different in FFPE groups.…”
Section: Discussionmentioning
confidence: 99%